Oven-Dried Cupuaçu and Bacuri Fruit Pulps as Amazonian Food Resources - Anna Paula Pereira Barbosa-Carvalho; Rosinelson da Silva Pena; Renan Campos Chisté (Resources)
The Amazon is one of the largest and most diverse biomes on the planet. Cupuaçu (Theobroma grandiflorum (Willd. ex Spreng.) Schum) and bacuri (Platonia insignis Mart.) are Amazonian fruit species appreciated for their sensory characteristics and promising availability of bioactive compounds. However, high moisture levels (>80%) make these pulps susceptible to deterioration during storage. In this study, the oven-drying process was monitored to produce dry and more stable pulps. The process was monitored at 40 °C, 55 °C and 70 °C, and the bioactive compounds and antioxidant capacity were determined as quality indicators. In general, drying at 70 °C for 340 min produced dried cupuaçu and bacuri pulps with high levels of total phenolic compounds: 288 and 652 mg gallic acid equivalents/100 g, respectively. The hygroscopic evaluation suggested that both of the dried pulps should be stored at a relative humidity of <40% to avoid rapid water adsorption and it is advised to carry out the oven-drying process until up to 12% moisture is reached for cupuaçu and 9% for bacuri to avoid unnecessary energy consumption. Thus, this study expands the potential of bacuri and cupuaçu pulps for application in food industries, contributing to the economic and social development of the Amazon region.